Coca leaves in the context of the central Andean Wari state - Valdez, Lidio M.; Taboada, Juan (My University, 2013)
The Middle Horizon (ca. 550 – 1100 CE) was a period during which the Wari State emerged in the Peruvian central highland valley of Ayacucho and expanded beyond its heartland to exercise political and economic control over most of the Central Andes. One of the probable reasons for the expansion of Wari was to establish direct access over the resources of other regions, including the tropical forest region. In addition to the unprecedented finding of the burial of an elite Wari leader at Vilcabamba, east of the Apurimac Valley, archaeological research carried out in the Apurimac Valley has shown that the Wari State successfully colonized the region. In the particular case of Apurimac Valley, it has been suggested that the establishment of Wari settlements in the tropical forest region was in order to access local products, in particular coca leaves. Until recently, only indirect evidence indicated the use of coca leaves by the inhabitants of the Wari State. New evidence coming from a Wari settlement in the highlands, consisting in the fortuitous and unprecedented finding of coca leaves in association with Wari material culture, confirms that the Wari State produced and consumed coca leaves and that this product was likely transported from the Apurimac Valley.
Presented on November 7–11, 2013 at the 46th Annual Chacmool Archaeology Conference: Trading Spaces: the Archaeology of Interaction, Migration and Exchange held at the University of Calgary in Calgary, Alberta.
Keywords: coca leaves; Wari State; Middle Horizon; Apurimac Valley; Peru